PKM Pemanfaatan Limbah Ampas Tebu dan Ampas Kopi: Implementasi Dukungan Penerapan SDG’s (12) - Putri, Putu Yudha Asteria; I Gede Nyoman Carlos W. Mada; Putu Ayu Sriasih Wesna (Politeknik Sahid, 2025)
ABSTRACTThis Community Partnership Program (PKM) was implemented in Padangsambian Village, Bali, as an effort to support the 12th Sustainable Development Goal (SDG) on responsible consumption and production. The program focused on utilizing sugarcane and coffee pulp waste into value-added products, such as recycled paper, through appropriate technology, education, and community empowerment. The implementation methods included technical training, demonstrations of simple tools, support for digital marketing, and institutional strengthening through basic accounting guidance and assistance with Intellectual Property Rights (IPR) registration. The results showed a significant increase in the community's capacity to manage waste independently and productively, the emergence of new economic opportunities, and increased environmental awareness. This program successfully created social and economic innovation at the community level, reinforcing the circular economy and supporting the reduction of organic waste at the local level. Future recommendations include strengthening local business institutions, expanding market access, providing legal assistance for product certification and IPR, and replicating the model in other villages with similar waste potential. This PKM serves as a concrete example of synergy between appropriate technology, community empowerment, and sustainable development goals. Keywords: waste management, SDG 12, sugarcane pulp, coffee pulp, community empowerment, circular economy. ABSTRAK Program Kemitraan Masyarakat (PKM) ini dilaksanakan di Desa Padangsambian, Bali, sebagai upaya mendukung tujuan Sustainable Development Goals (SDGs) ke-12 tentang konsumsi dan produksi yang bertanggung jawab. Kegiatan ini difokuskan pada pemanfaatan limbah ampas tebu dan kopi menjadi produk bernilai tambah, seperti kertas daur ulang, melalui pendekatan teknologi tepat guna, edukasi, dan pemberdayaan masyarakat. Metode pelaksanaan melibatkan pelatihan teknis, demonstrasi alat sederhana, pendampingan pemasaran digital, serta penguatan kelembagaan melalui bimbingan akuntansi sederhana dan pengurusan HAKI. Hasil kegiatan menunjukkan peningkatan signifikan dalam kapasitas masyarakat untuk mengelola limbah secara mandiri dan produktif, munculnya peluang ekonomi baru, serta peningkatan kesadaran lingkungan. Program ini berhasil menciptakan inovasi sosial dan ekonomi berbasis komunitas, yang memperkuat ekonomi sirkular dan mendukung pengurangan limbah organik di tingkat lokal. Rekomendasi ke depan mencakup penguatan kelembagaan, pengembangan akses pasar, pendampingan legalitas usaha, dan replikasi model ke desa lain dengan potensi serupa. PKM ini menjadi contoh nyata sinergi antara teknologi sederhana, pemberdayaan masyarakat, dan tujuan pembangunan berkelanjutan. Kata kunci: pengelolaan limbah, SDGs 12, ampas tebu, ampas kopi, pemberdayaan masyarakat, ekonomi sirkular.